Desarrollo y simulación de un sistema multiagente para la comunicación de semáforos para encontrar la ruta óptima mediante grafos. - Loarte Caraguay, Robert Iván, Bolívar Rolando Quizhpe Vásquez (2016)
Nowadays a there is a new interest in the development of technology for the implementation of intelligent cities and provide solutions to problems on the daily living. One of those problems is the vehicular traffic that exist in cities, although it is true there are traffic lights to control traffic, but they are incapable of making decisions for themselves in cases of any agglomerations or accidents happens, that causes great disadvantages for both drivers and pedestrians economically, and the impact to the environment. Under these circunstances, the following research paper discuss the development and simulation of a multi-agent system that will be represented by the traffic lights in order that these devices get tp communicate through a stablished language and make decisions autonomously, it has been developed through a architecture called BDI (Beliefs: Beliefs, Desires: Desires, Intentions: Intentions) and through JADE (Framework for the development of agents in Java) with FIPA-ACL that supports the coordination of multiple agents and provides a standard language of communication between them. Traffic lights communicate when an event occurs, for example: Car accidents, agglomeration and when a new agent exists; nearby traffic lights communicate with the traffic lights where the accident took place. Whenever there is an accident or agglomeration, these lights will be marked on the map, giving the user the possibility to avoid those traffic lights and plotting a route to his/her destination.